Collateral consequences of the school-to-prison pipeline: Adolescent substance use and developmental risk. (February 2023) - Prins, Seth J.; Shefner, Ruth T.; Kajeepeta, Sandhya; Hatzenbuehler, Mark L.; Branas, Charles C.; Metsch, Lisa R.; Russell, Stephen T.
Highlights: Adolescent health consequences of exclusionary school discipline are underexplored. We created an unprecedented dataset linking student health and discipline measures. School prevalence of discipline predicted higher school-mean substance use. School prevalence of discipline predicted lower school-mean social support. Exclusionary discipline likely drives adolescent substance use/developmental risk. Abstract: Objective: The adolescent health consequences of the school-to-prison pipeline remain underexplored. We test whether initiating components of the school-to-prison pipeline—suspensions, expulsions, and school policing—are associated with higher school-average levels of student substance use, depressed feelings, and developmental risk in the following year. Method: We linked 2003–2014 data from the California Healthy Kids Survey and the Civil Rights Data Collection from over 4, 800 schools and 4, 950, 000 students. With lagged multi-level models, we estimated relationships between the school prevalence of total discipline, out-of-school discipline, and police-involved discipline, and standardized school-average levels of 6 substance use measures and 8 measures of developmental risk, respectively. Results: The prevalence of school discipline predicted subsequent school-mean substance use and developmental risk. A one-unit higher prevalence of total discipline predicted higher school levels (in standard deviations) of binge drinking alcohol (0.14, 95% CI: 0.11, 0.17), drinking alcohol (0.15, 95% CI: 0.12, 0.18), smoking tobacco (0.09, 95% CI: 0.06, 0.12), using cannabis (0.16, 95% CI: 0.14, 0.19), using other drugs (0.17, 95% CI: 0.14, 0.21), and violence/harassment (0.16, 95% CI: 0.12, 0.2). Total discipline predicted lower levels of reported community support (−0.07, 95% CI: −0.1, −0.05), feeling safe in school (-0.12, 95% CI: −0.16, −0.09), and school support (−0.16, 95% CI: −0.19, −0.12). Associations were greater in magnitude for more severe out-of-school discipline. Findings were inconsistent for police-involved discipline. Conclusion: Exclusionary school discipline and school policing—core elements of the school-to-prison pipeline—are previously unidentified population predictors of adolescent substance use and developmental risk.